2001
DOI: 10.1161/01.cir.103.25.3081
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pacemaker Dependency and the Effect of Pacing Mode on Cardiovascular Outcomes

Abstract: This study demonstrated that UHR at first follow-up has an important influence on how pacing mode selection affects cardiovascular death and total mortality. Pacemaker-dependent patients with low UHR will probably be paced frequently and will likely benefit from physiological pacing. In contrast, non-pacemaker-dependent patients will likely be paced infrequently and may not benefit from physiological pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 12 publications
3
55
0
2
Order By: Relevance
“…No individual trial showed a significant difference in all-cause or cardiovascular mortality ( In CTOPP, pacemaker dependency was defined as the presence of an underlying spontaneous heart rate of less than 60 bpm. 57 A significant increased risk of death was found in pacemaker-dependent individuals paced with ventricular pacemakers (7.8%) compared with physiological pacing (4.6%), a relative risk reduction of 38% (95% CI 18 to53%, p < 0.001), but an absolute risk reduction of 3.2%, corresponding to a number needed to treat (NNT) of 31. Mortality in non-pacemaker-dependent individuals was not significantly different.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…No individual trial showed a significant difference in all-cause or cardiovascular mortality ( In CTOPP, pacemaker dependency was defined as the presence of an underlying spontaneous heart rate of less than 60 bpm. 57 A significant increased risk of death was found in pacemaker-dependent individuals paced with ventricular pacemakers (7.8%) compared with physiological pacing (4.6%), a relative risk reduction of 38% (95% CI 18 to53%, p < 0.001), but an absolute risk reduction of 3.2%, corresponding to a number needed to treat (NNT) of 31. Mortality in non-pacemaker-dependent individuals was not significantly different.…”
Section: Mortalitymentioning
confidence: 99%
“…In CTOPP, pacemaker dependency was indirectly assumed to be present in individuals with underlying spontaneous heart rate lower then 60 bpm during ventricular pacing and measured at baseline. The CTOPP substudy on pacemaker dependency 57 was invalidated by the exclusion of participants for whom end-points had occurred before measurement of underlying spontaneous heart rate. Conclusions from this study should be considered very cautiously.…”
Section: Ancillary Studies and Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…31) In spite of lacking the reduction of mortality in physiological pacing, subgroup analysis showed beneficial effect on combined end point of stroke or cardiovascular death, as well as cardiovascular-death and total mortality in pacemaker dependent group but not in non-pacemaker dependent group. 32) In addition, this study reported that unpaced heart rate at first follow-up has an important influence on cardiovascular death and total mortality. Ongoing pacing trial like as the Danish Multicenter Randomized Study (DANPACE) 33) and the United Kingdom Pacing and Clinical Event Trial (UKPace) 34) may provide prospective data on the relation between underlying heart rate and pacing mode selection in view point of mortality.…”
Section: J Arrhythmia Vol 21 No 4 2005mentioning
confidence: 81%
“…This study reported that those with an unpaced heart rate Ͻ60 bpm benefited from physiological pacing, with a significant reduction in the incidence of cardiovascular death or stroke. 3 A small, randomized study of atrial versus ventricular pacing in patients with sinus node dysfunction, the Danish Study, initially reported no benefit of physiological (AAI) pacing at a mean follow-up of 3 years. 4 However, after a more extended follow-up of 5.5 years, significant reductions in death and in atrial fibrillation were reported.…”
mentioning
confidence: 99%